2016
DOI: 10.1088/0031-9155/61/17/6413
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characteristics of four PTW microDiamond detectors in high-energy proton beams

Abstract: Small diamond detectors are useful for the dosimetry of high-energy proton beams. However, linear energy transfer (LET) dependence has been observed in the literature with such solid state detectors. A novel synthetic diamond detector has recently become commercially available from the manufacturer PTW-Freiburg (PTW microDiamond type 60019). This study was designed to thoroughly characterize four microDiamond detectors in clinical proton beams, in order to investigate their response and their reproducibility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 36 publications
0
34
1
Order By: Relevance
“…In Ref. , the evaluation of four microDiamonds indicates that the microDiamond detectors are not reproducible and presented differences in terms of stability, sensitivity, and LET dependence. The LET dependence is in contrast with other studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. , the evaluation of four microDiamonds indicates that the microDiamond detectors are not reproducible and presented differences in terms of stability, sensitivity, and LET dependence. The LET dependence is in contrast with other studies .…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, quenching effects may occur in regions with increased LET and therefore solid detectors must be used carefully. Diamond detectors are tissue equivalent and therefore could be of high interest in future . The microDiamond TM60019 (PTW, Freiburg), which offers an effective thickness of 1 μ m, a radius of 1.1 mm and a volume of 0.004 mm 3 , has been used for reference transverse profile acquisitions in water for TPS commissioning.…”
Section: Methodsmentioning
confidence: 99%
“…The observed decrease in RQ/RQ0 at the effective photon energy of 13.9 keV (25 kV beam spectrum) could be due to detector under‐response when the linear energy transfer (LET) of secondary electrons increases. An under‐response of a microDiamond was reported in high‐LET carbon and oxygen beams, but in proton beams the reported results were inconclusive indicating either no significant LET dependence or under‐response …”
Section: Discussionmentioning
confidence: 99%
“…Recently, diamond detectors have regained interest because the current manufacturing technology allows for reproducible high‐purity crystal growth. Commercially available synthetic diamond detectors microDiamond (PTW 60019, Freiburg, Germany) have been used in small‐field dosimetry of high‐energy photon and electron beams, as well as in proton and carbon beams . These studies showed that the detectors have low absorbed‐dose energy dependence, negligible dose‐rate dependence and do not require high pre‐irradiation doses (up to 2 Gy).…”
Section: Introductionmentioning
confidence: 99%
“…Also in protons, most dosimetry studies conclude that the response of the PTW‐60019 microDiamond detector exhibits no LET dependence nor quenching effect (Mandapaka et al, Marinelli et al, Yuichi et al, Rossomme et al, Akino et al). In, which is based on an intercomparison of four microDiamond detectors in a clinical 138 MeV proton beam, authors reported a nonreproducibility between devices in terms of stability, sensitivity, and LET dependence. The response of the PTW‐60019 microDiamond detector has been little investigated in carbon ion beams.…”
Section: Introductionmentioning
confidence: 99%